White Adipose Tissue Expansion in Multiple Symmetric Lipomatosis Is Associated with Upregulation of CK2, AKT and ERK1/2 - Sanna, Marta (Int J Mol Sci, 2020)
Multiple symmetric lipomatosis (MSL) is a rare disorder characterized by overgrowing lipomatous tissue (LT) in the subcutaneous adipose tissue (SAT). What LT is and how it expands are not completely understood; previous data suggested that it could derive from brown AT precursors. In six MSL type I patients, we compared LT morphology by histological and immunohistochemistry (IHC) analysis, gene expression, by qPCR, kinase activity, by Western Blot and in vitro assay to paired-control SAT using AT from patients with pheochromocytoma as a human browning reference. In the stromal vascular fraction (SVF), we quantified adipose stem cells (ASCs) by flow cytometry, the proliferation rate, white and beige adipogenic potential and clonogenicity and adipogenicity by a limiting dilution assay. LT displayed white AT morphology and expression pattern and did not show increased levels of the brown-specific marker UCP1. In LT, we evidenced AKT, CK2 and ERK1/2 hyperactivation. LT-SVF contained increased ASCs, proliferated faster, sprouted clones and differentiated into adipocytes better than the control, displaying enhanced white adipogenic potential but not increased browning compared to SAT. In conclusion, LT is a white AT depot expanding by hyperplasia through increased stemness and enhanced white adipogenesis upregulating AKT, CK2 and ERK1/2, which could represent new targets to counteract MSL.